Datil Pepper Summer Sausage: An Innovative Product Using Florida Datil Peppers - Sally K. Williams; Noufoh Djeri; Edsel Redden; David Dinkins; David Bearl (EDIS)
AN220, a 4-page fact sheet by Sally K. Williams, Noufoh Djeri, Edsel Redden, David Dinkins, and David Bearl, describes a new summer sausage product featuring the datil pepper, which has been grown in the St. Augustine area for around 230 years — the formulation and the results of taste tests. Includes references. Published by the UF Department of Animal Sciences, July 2009.